(untitled) (Management and Connections Journal, 2024)
The high levels of unemployment and the disruption of the labor market were conducive to strengthening entrepreneurship and informality in the country, as a solution for the unemployed contingent. This way of entering the market mainly attracts young people who see this alternative as a way of obtaining income. In this sense, this article sought to verify the factors that influenced young people to be informally self-employed. The approach was qualitative, and whose research strategy used was the biographical method, through analysis of the life history of five young people from the city of Aracaju-SE. The results show that young informal self-entrepreneurship occurred mostly out of necessity, due to socioeconomic conditions, such as low education and unemployment, and also the desire for autonomy and independence at work.